THE EVALUATION OF INCREASED SERUM CREATININE DUE TO THE USE OF ACEI THERAPY ON HYPERTENSION PATIENTS IN UNDATA HOSPITAL, PALU, CENTRAL SULAWESI PROVINCE - RUMI, AMELIA; M RADI, DAN NURHALIMA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study aims to determine the mean baseline value and the evaluation of serum creatinine in hypertensive patients after receiving angiotensin-converting enzyme inhibitor (ACEi) antihypertensive therapy for the first time in a span. Methods: This study used a cross-sectional design with a prospective approach by carrying out laboratory tests of serum creatinine using the Jaffe method using the patient’s blood at the beginning as the baseline value and a month after treated with (ACEi) antihypertensive therapy as the evaluation value. The results of this research were analyzed using the SPSS statistical paired test to observe the occurrence of increased serum creatinine as the aftereffect of ACEi antihypertensive treatment. The total of samples which met the inclusion and exclusion criteria was 30 patients. Results: The findings showed an increase of serum creatinine value, where statistics displayed the significant value of **P below 0.05 with the mean baseline value of 0.98 and an average evaluation value of 1.14. When examined clinically, despite the increase of serum creatinine, the patient’s kidney function is still within a normal range. Conclusion: The study concluded that the increase of serum creatinine value can become one’s indicators of decreasing kidney function.